2022
DOI: 10.20870/oeno-one.2022.56.3.5466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early cane pruning on yield components, grape composition, carbohydrates storage and phenology in <i>Vitis vinifera</i> L. cv. Merlot

Abstract: Dormant cane pruning has a great impact on vineyard management both in terms of labour costs and the time required to complete this field operation in the absence of mechanisation. In this study, we investigated over three seasons the influence of five pruning dates on yield components, grape composition, phenology and carbohydrate reserves in the variety Merlot, grown in a warm climate area. Pruning was conducted soon after harvest, at the end of leaf fall, two bud dormancy stages and vine bleeding. Early pru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…An assay of TNCs (sucrose, glucose, and fructose) on the thick roots was performed owing to the importance of TNCs in subsequent years for accumulation of starch reserves [37]. Briefly, TNCs were assessed using anthrone reagent (Merck, Darmstadt, Germany) and absorbance readings at 620 nm were performed using a Shimadzu UV Mini-1240 spectrophotometer (Kyoto, Japan) [38]. The data are expressed in mg g −1 DW.…”
Section: Measurement Of Total Non-structural Carbohydrates (Tncs)mentioning
confidence: 99%
“…An assay of TNCs (sucrose, glucose, and fructose) on the thick roots was performed owing to the importance of TNCs in subsequent years for accumulation of starch reserves [37]. Briefly, TNCs were assessed using anthrone reagent (Merck, Darmstadt, Germany) and absorbance readings at 620 nm were performed using a Shimadzu UV Mini-1240 spectrophotometer (Kyoto, Japan) [38]. The data are expressed in mg g −1 DW.…”
Section: Measurement Of Total Non-structural Carbohydrates (Tncs)mentioning
confidence: 99%
“…In addition, high temperatures during fruit development can promote hypoxia in the berry, and, consequently, increase the respiration of mesocarp cells (Greer, 2017). All these alterations may promote modi cation of the cell wall structure, and composition of berries by enzymes, as reported in white grape genotypes (Airén, Albillo Dorado, and Montonera del Casar) (Perez-Navarro et al, 2021), and purple grape (Merlot) (Falginella et al, 2022).…”
Section: Discussionmentioning
confidence: 97%
“…'Malbec' (Ferrara et al, 2022;Morgani et al, 2022), 'Merlot' (Allegro et al, 2020), 'Bobal' and 'Tempranillo' (Buesa et al, 2020), and Pinot Noir (Frioni et al, 2019). In contrast, Falginella et al (2022) reported that yield and qualitative parameters are not affected by different growing seasons in hot climate regions. Although some effects can be noticed in early maturing cultivars, the vine's recovery from late phenological stages is reduced ring the growing season.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations